Effectiveness and safety of nurse-led different epidural analgesia methods based on symptom management theory in patients with severe acute pancreatitis: A single-center RCT protocol - You Yuan; Qian Luo; Feiyu Yan; Li Li; Lifeng He; Yan Zhou; Chunlan Wu; Mingli Zhong; Fang Chen; Xia Zhang; Junxi Chen; Bao Fu; et al. (PLoS ONE, 2026)
Background Patients with severe acute pancreatitis (SAP) often experience intense pain that significantly impacts their quality of life and may hinder recovery. Current pain management approaches have limitations. Although continuous thoracic epidural analgesia (TEA) is generally effective, some patients still need additional intermittent injections of local anesthetics for sufficient pain relief. In the ICU, nurses are the primary providers responsible for pain management. Symptom Management Theory (SMT), though used in various fields, has not yet been fully validated for nurse-led pain management employing different TEA administration methods in SAP. Objective This protocol aims to assess the effectiveness and safety of SMT-based nurse-led TEA administration methods in patients with SAP, with the goal of optimizing pain management protocols. Methods and analysis This single-center, randomized, controlled clinical trial will enroll 76 patients with SAP, randomized into two groups (N = 38 each). The control group will receive continuous TEA with a 50 ml mixture containing nalbuphine 40 mg, ropivacaine 225 mg, lidocaine 0.2 g, and 6 ml of 0.9% saline, administered at 3–5 ml/h. If the patient’s pain score (VAS-P) exceeds 3 or becomes intolerable, the infusion rate will be increased by 1–2 ml/h. In the experimental group, under SMT-guided nurse-led TEA management, nurses will report pain scores exceeding 3 to physicians, and intermittent epidural injections of 5 ml of the same mixture will be administered according to medical prescription, at intervals of ≥2 hours. Pain responses and patient feedback will be continuously monitored to guide timely adjustments of analgesics. The primary outcome is VAS-P. Secondary outcomes include intra-abdominal pressure (IAP), total dose of combined medication, number of additional interventions, duration of epidural placement, and incidence of 16 predefined adverse events. Endpoint outcomes consist of puncture success rate, ICU length of stay, 28-day mortality, and patient satisfaction with analgesia. Data will be analyzed using SPSS. Repeated measures data (e.g., VAS-P and IAP at 0 h, 1 h, 6 h, 12 h, 24 h, 48 h, and 72 h) will be examined with a multivariate mixed-effects repeated measures model (MMRM), which appropriately handles data missing at random. Other secondary outcomes, adverse events, and endpoint measures will be analyzed with descriptive statistics, and between-group comparisons will be conducted using t-tests, Mann-Whitney U tests, χ² tests, or Fisher’s exact tests, as appropriate. Expected conclusion The experimental group is anticipated to demonstrate superior pain management outcomes compared to the control group, with no increase in adverse events. The SMT-based nurse-led TEA protocol is expected to be safe and effective in improving analgesia, reducing ICU length of stay, decreasing 28-day mortality, and enhancing patient satisfaction. This study will provide new insights and methods for pain management in SAP patients, thereby promoting optimization of clinical practice.